Phase I/II intra-patient dose escalation study of vorinostat in children with relapsed solid tumor, lymphoma or leukemia - Witt, Olaf; Milde, Till; Deubzer, Hedwig; Oehme, Ina; Kulozik, Andreas; Eisenmenger, Andreas; Abel, Ulrich; Karapanagiotou-Schenkel, Irini (Klinische Pädiatrie, 2012)
Members of the histone deacetylase (HDAC) family exhibit great promise as potential drug targets in pediatric tumors including neuroblastoma, medulloblastoma, ependymoma and Ewing’s sarcoma. HDAC inhibitors of various structural classes have shown anti-tumoral effects in pre-clinical pediatric tumor models as single agents or in combination treatments. Suberoylanilidehydroxamic acid (SAHA=vorinostat) is the most clinical advanced compound of the class and was approved by the US FDA in October 2006 for the treatment of refractory cutaneous T-cell lymphoma. In this phase I/II trial, pediatric patients with relapsed solid tumors, lymphoma or leukemias are treated according to an individualized dose escalation concept ensuring each individual patient to receive his optimal dose with respect to toxicity and efficacy. The study is accompanied by an extensive pharmacokinetic, pharmacodynamic and biomarker program.